Environmental Disclosures in Financial Statements and Management Reports on the Example of Energy Sector Companies in Poland - Małgorzata KOŻUCH; Renata ŻABA-NIERODA (Communications of International Proceedings, 2021)
Environmental information contained in the financial statements is insufficient in the context of increased demand for it, therefore more and more attention is being paid to the possibilities offered by the activity report and environmental reports in this respect. The aim of the article is to identify and characterize selected initiatives of enterprises from the energy sector in the field of environmental protection, implemented as part of the responsible business strategy and to make this information visible in the management report, integrated report or other non-financial information.
Keywords: Corporate Social Responsibility; Energy Sector; Sustainable Development; Management Report.